Nitrile hydrolysis in a rhenium(I)-ruthenium(III) dinuclear complex - Fagalde, Florencia (2004)
Kinetic data for the hydrolysis reaction: [(CO)3(bpy)Re I(4-CNpy)RuIII(NH3)5]4+ + H2O → [(CO)3(bpy)ReI(4-C(O)NHpy)Ru III(NH3)5]3+ + H+ (bpy = 2,2′-bipyridine, 4-CNpy = 4-cyanopyridine and 4-C(O)NHpy = isonicotinamido), that occurs after oxidation with S2O 82- of the dinuclear species [(CO)3(bpy)Re I(4-CNpy)RuII (NH3)5]3+, have been obtained in aqueous solutions by spectrophotometric techniques. The observed rate constant, kh = (8.6 ± 0.5) × 10 -3 s-1, at 25°C, pH = 3.0 (CF3COOH) and I = 0.1 M (KCl), is ca. three times higher than the corresponding one for the mononuclear complex [(4-CNpy)RuIII(NH3)5] 3+, indicating that the catalytic effect of the Ru III(NH3)5 moiety is enhanced by coordination of the free N of 4-CNpy to the ReI(CO)3(bpy) moiety. The value of kh is even higher than that of the dinuclear complex [(trpy)(bpy)RuII (4-CNpy)RuIII(NH3) 5]5+ (trpy = 2,2′:6′,2″-terpyridine), reflecting the fact that carbonyls are much stronger π-acceptors than polypyridines.